Theorizing: A Phenomenological, Theoretical, and Quantitative Case Study - Doner, Jonathan (International Review of Theoretical Psychologies, 2026)
A theory is discussed which attempts to provide a basic understanding of the work of theorizing. It is developed from an analysis of the author’s own experience. According to this theory, theorizing consists, fundamentally, in a series of intellectual engagements. Each engagement begins with the theorist selecting and performing an epistemic, or knowledge seeking, behavior. In doing so, the theorist activates associated cognitive operations. These always begin with attention and interpretation, followed by thoughts, memories, images, or whatever information-based procedures the theorist is utilizing. Cognitive operations write information into a theory space where it is immediately subject to the forces of the theory space’s field—expansion, integration, and contextualization. The purpose and consequence of this process is the development of a network of connections between the theory and its ground. Repeated engagements result in the theory space becoming an integral whole, not simply a collection of ideas. A mature theory space is marked by precise statements of the ground and theory, along with an information-rich, well-articulated support network.